ANALISIS KOMPARATIF PROFITABILITAS SEBELUM DAN SAAT COVID-19 PADA PERUSAHAANA SUB-SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INFONESIA: Covid-19, Kinerja Keuangan, Profitabilitas, Net Profit Margin, Return On Asset, Return On Equity - Musfiah Afiati Mufli; Salida, Amrizal; Taufiq, Muhammad (Paser Institute Of Accounting and Finance, 2024)
The COVID-19 pandemic, which began in late 2019, caused Indonesia's economic growth to contract, with lockdowns and PPKM (Community Activity Restrictions) having a negative impact on the revenues of several industrial sectors, except for the healthcare sector, which was the main driver of revenue decline. This is due to the significant role the healthcare sector played in addressing the disease. Therefore, this study aims to analyze and compare whether there are significant differences in productivity before and during the COVID-19 pandemic among companies in the welfare sub-sector listed on the Indonesia Stock Exchange, using metrics such as Net Total Revenue, Return On Resources, and Return On Value. The comparative analysis employs a quantitative descriptive method. The data for this research comes from secondary sources, specifically the Indonesia Stock Exchange and financial reports of ten companies published on their official websites, using purposive sampling. The investigation strategy involves using an appropriate t-test. Based on the findings, healthcare subsector companies showed no significant difference in Net Profit Margin, Return On Assets, and Return On Equity between the period of 2018 (before the COVID-19 pandemic) and 2020 (during the COVID-19 pandemic). Essentially, welfare sector organizations remained stable in the face of the limitations caused by the COVID-19 pandemic. However, to avoid potential worst-case scenarios that could harm businesses, it is hoped that business operators will always be prepared to face changes or conditions beyond predictions.